Molecular Behavior of HMGB1 in the Cochlea Following Noise Exposure and in vitro - Xiao, Lili; Sun, Yan; Liu, Chengqi; Zheng, Zhong; Shen, Ying; Xia, Liang; Yang, Guang; Feng, Yanmei (Frontiers in Cell and Developmental Biology, 2021)
Noise-induced hearing loss (NIHL) is characterized by cellular damage to the inner ear, which is exacerbated by inflammation. High-mobility group box 1 (HMGB1), a representative damage-associated molecular pattern (DAMP), acts as a mediator of inflammation or an intercellular messenger according to its cellular localization. Blocking or regulating HMGB1 offers an attractive approach in ameliorating NIHL. However, the precise therapeutic intervention must be based on a deeper understanding of its dynamic molecular distribution and function in cochlear pathogenesis after acoustic trauma. Here, we presented the spatiotemporal dynamics of the expression of HMGB1, exhibiting distribution variability in specific cochlear regions and cells following noise exposure. Following gene manipulation, we further investigated the characteristics of cellular HMGB1 in HEI-OC1 cells. The higher cell viability observed in the HMGB1 knocked-down group after stimulation with H2O2 indicated the possible negative effect of HMGB1 on cellular lifespan. In conclusion, this study demonstrated that HMGB1 is involved in NIHL pathogenesis and its molecular biology has essential and subtle influences, preserving a translational potential for pharmacological intervention.